Competencies Required to Deliver a Primary Healthcare Approach in the Occupational Therapy: A South African Perspective - Deshini Naidoo; Jacqueline Marina Van Wyk (Occupational Therapy International, 2023)
Introduction. The South African government introduced a reengineered primary healthcare approach to promote universal health coverage. The approach was to ensure equitable, efficient, and quality health services for consumers in private and public healthcare sectors. The transition toward a more comprehensive primary healthcare approach to intervention requires occupational therapists who predominantly worked in private and hospital settings to extend their services to clients who previously would have had little access to such services. This study was conducted to identify the key competencies required by occupational therapists to deliver appropriate primary healthcare services to communities from previously disadvantaged periurban and rural areas. Methods. An exploratory, qualitative study design was used. Through the use of policy documents and data from key informants (n=5), established therapists (n=14), and novice occupational therapy graduates (n=39), the study identified and mapped the stakeholders’ perspectives of the competencies required by graduates to practice in periurban and rural settings in KwaZulu-Natal in South Africa. Data was collected using semistructured interviews, a focus group discussion, a document review of the university’s curriculum, and the local and global regulatory documents. A framework based on the seven roles of the university’s competency framework informed the data analysis process. The seven roles are health practitioner, communicator, collaborator, health advocate, leader and management, scholar, and professional. Findings. Participants highlighted the need for graduates to have adequate knowledge and understanding of the impact of the Department of Health policies and social determinants of health on occupation and the client’s health. They also needed to be suitably skilled in culturally sensitive communication, negotiating shared goals with the stakeholders, and managing a department. Graduates needed to be socially accountable and develop services to advocate for their clients. Conclusion. The study offered insights into the essential graduate competencies identified by the stakeholders and recommended measures to prepare rehabilitation graduates for service delivery in primary healthcare contexts.